INVESTIGATING FACTORS THAT AFFECT THE CONTINUANCE USE INTENTION AMONG THE HIGHER EDUCATION INSTITUTIONS’ LEARNERS TOWARDS A GAMIFIED M-LEARNING APPLICATION - Roslan, Rosfuzah; Mohd Ayub, Ahmad Fauzi; Ghazali, Norliza; Zulkifli, Nurul Nadwa; Md Latip, Siti Noor Haslina; Abu Hanifah, Siti Syuhada (jiter, 2023)
Future studies could include respondents from other diploma programmes, resulting in an in-depth analysis. It is needed to support the generalizability of the findings in this study by considering larger populations from all different programmes. In addition, similar research can be done based on different circumstances; for instance, use of the gamified m-learning application during the incampus physical classes instead of virtual classes (online), which might influence the users’ perception in terms of the social influence and facilitating condition.